2021
DOI: 10.3389/frobt.2021.738214
|View full text |Cite
|
Sign up to set email alerts
|

Yoshimura-origami Based Earthworm-like Robot With 3-dimensional Locomotion Capability

Abstract: Earthworm-like robots have received great attention due to their prominent locomotion abilities in various environments. In this research, by exploiting the extraordinary three-dimensional (3D) deformability of the Yoshimura-origami structure, the state of the art of earthworm-like robots is significantly advanced by enhancing the locomotion capability from 2D to 3D. Specifically, by introducing into the virtual creases, kinematics of the non-rigid-foldable Yoshimura-ori structure is systematically analyzed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 54 publications
0
10
0
2
Order By: Relevance
“…For manufacturing, we chose thin films as the origami material [50,57,58], with the advantages of lightness, safety, flexibility, and durability, including polyethylene terephthalate (PET), polyimide (PI) and polytetrafluoroethylene (PTFE). Because of the lack of stability of single-layer films, we constructed double-layer films that are bonded with double-sided adhesive, and the creases were machined by laser machining techniques.…”
Section: Origami Structural Designmentioning
confidence: 99%
“…For manufacturing, we chose thin films as the origami material [50,57,58], with the advantages of lightness, safety, flexibility, and durability, including polyethylene terephthalate (PET), polyimide (PI) and polytetrafluoroethylene (PTFE). Because of the lack of stability of single-layer films, we constructed double-layer films that are bonded with double-sided adhesive, and the creases were machined by laser machining techniques.…”
Section: Origami Structural Designmentioning
confidence: 99%
“…Moreover, the mechanical response of origami is sensitive to factors such as material properties and geometric design [1]. For example, the torsional stiffness of rigid origami can be alternated by tuning the thickness of the single folding joint [43]; the folding response of a paper-based Kresling tower can be adjusted between monostable and bistable behavior by tailoring the geometric parameters [44,33]. Consequently, the response of the Kresling tower under various of mechanical conditions has been thoroughly characterized.…”
Section: Experimental Characterizationmentioning
confidence: 99%
“…In addition, the unique behaviour of the origami structure can also be utilized for soft robotic actuator applications Pagano et al, 2017. For example, Zhang et al (2021) described the design and implementation of a soft, earthworm-like robot that utilizes a non-rigid folding pattern of the Yoshimura structure to achieve 3-dimensional locomotion. Similarly, Kaufmann et al (2022) reported the development of a new type of robotic arm utilizes Kresling origami-inspired design principles to achieve high levels of flexibility and manoeuvrability.…”
Section: Introductionmentioning
confidence: 99%